Depressive Symptoms and Total Healthcare Costs: Roles of Functional Limitations and Multimorbidity. Issue 8 (23rd March 2019) - Schousboe, John T.; Vo, Tien N.; Kats, Allyson M.; Langsetmo, Lisa; Diem, Susan J.; Taylor, Brent C.; Strotmeyer, Elsa S.; Ensrud, Kristine E.
Abstract : OBJECTIVES: Depressive symptoms can be both a cause and a consequence of functional limitations and medical conditions. Our objectives were to determine the association of depressive symptoms with subsequent total healthcare costs in older women after accounting for functional limitations and multimorbidity. DESIGN: Prospective cohort study (Study of Osteoporotic Fractures [SOF]). SETTING: Four US sites. PARTICIPANTS: A total of 2508 community‐dwelling women (mean age = 79.4 years) participating in the SOF year 10 (Y10) examination linked with their Medicare claims data. MEASUREMENTS: At Y10, depressive symptoms were measured using the 15‐item Geriatric Depression Scale (GDS) and functional limitations were assessed by number (range = 0‐5) of impairments in performing instrumental activities of daily living. Multimorbidity was ascertained by the Elixhauser method using claims data for the 12 months preceding the Y10 examination. Total direct healthcare costs, outpatient costs, acute hospital stays, and skilled nursing facility during the 12 months following the Y10 examination were ascertained from claims data. RESULTS: Annualized mean (SD) total healthcare costs were 4654 (9075) in those with little or no depressive symptoms (GDS score = 0‐1), 7871 (14 534) in those with mild depressive symptoms (GDS score = 2‐5), and 9010 (15 578) in those with moderate to severe depressive symptoms (GDS score = 6 or more). After adjustment for age, site, self‐reported functional limitations, and multimorbidity, the magnitudes of these incremental costs were partially attenuated (cost ratio = 1.34 [95% confidence interval CI = 1.14‐1.59] for those with mild depressive symptoms, and cost ratio = 1.29 [95% CI = 0.99‐1.69] for those with moderate to severe depressive symptoms vs women with little or no depressive symptoms). CONCLUSION: Depressive symptoms were associated with higher subsequent healthcare costs attributable, in part, to greater functional limitations and multimorbidity among those with symptoms. Importantly, even mild depressive symptoms were associated with higher healthcare costs. J Am Geriatr Soc 67:1596–1603, 2019